Tomographic reconstructions of the fast-ion phase space using imaging neutral particle analyser measurements - Rueda-Rueda, J; Garcia-Munoz, M; Viezzer, E; Schneider, P A; Oyola, P; Galdon-Quiroga, J; Salewski, M; Schmidt, B S; Garcia-Dominguez, J (Plasma physics and controlled fusion, 2024)
In this paper we demonstrate how the inversion, in energy and major radius (E, R) coordinates, of imaging neutral particle analyser (INPA) measurements can be used to obtain the fast-ion distribution. The INPA is most sensitive to passing ions with energies in the range (20–150) keV and pitches near 0.5 in the core and 0.7 near the plasma edge. Inversion of synthetic signals, via 0th-order Tikhonov and Elastic Net regularization, were performed to demonstrate the capability of recovering the ground truth fast-ion 2D phase-space distribution resolved in major radius and energy, even in the presence of moderate noise levels (10%). Finally, we apply our method to measure the 2D phase-space distribution in an MHD quiescent plasma at ASDEX Upgrade and find good agreement with the slowing down fast-ion distribution predicted by TRANSP.